Force development against irregular and hybrid warfare in Indonesia (Defense and Security Studies, 2023)
The development of national defense is directed to be able to answer various possible threats and actual problems that are adjusted to the geographical conditions and dynamics of the strategic environment. Current and future threats are growing very fast and increasingly complex. Threats to the state can essentially be classified into three types, namely military threats, both armed and unarmed, non-military threats, and hybrid threats. The threats that have emerged during the COVID-19 pandemic are irregular warfare and hybrid threats. This research will discuss the analysis of force development to face the threat of irregular warfare and hybrid warfare in Indonesia. This research uses a qualitative method with a literature study approach. Based on the results of the study, it is concluded that Indonesia as a country that has a strategic location and attractiveness of various spectrums needs to always prepare itself by implementing relevant strategies in accordance with the capital already owned in the Indonesian nation itself, this is needed to avoid national disunity due to irregular warfare that enters the joints of state life.